Drug Enforcement Agency 2014 Hydrocodone Rescheduling Rule and Opioid Dispensing after Surgery. (May 2020) - Neuman, Mark D.; Hennessy, Sean; Small, Dylan S.; Newcomb, Craig; Gaskins, Lakisha; Brensinger, Colleen M.; Wijeysundera, Duminda N.; Bateman, Brian T.; Wunsch, Hannah
Abstract : Background: In 2014, the U.S. Drug Enforcement Agency reclassified hydrocodone from Schedule III to Schedule II of the Controlled Substances Act, resulting in new restrictions on refills. The authors hypothesized that hydrocodone rescheduling led to decreases in total opioid dispensing within 30 days of surgery and reduced new long-term opioid dispensing among surgical patients. Methods: The authors studied privately insured, opioid-naïve adults undergoing 10 general or orthopedic surgeries between 2011 and 2015. The authors conducted a differences-in-differences analysis that compared overall opioid dispensing before versus after the rescheduling rule for patients treated by surgeons who frequently prescribed hydrocodone before rescheduling ( i.e., patients who were functionally exposed to rescheduling's impact) while adjusting for secular trends via a comparison group of patients treated by surgeons who rarely prescribed hydrocodone ( i.e., unexposed patients). The primary outcome was any filled opioid prescription between 90 and 180 days after surgery; secondary outcomes included the 30-day refill rate and the amount of opioids dispensed initially and at 30 days postoperatively. Results: The sample included 65, 136 patients. The percentage of patients filling a prescription beyond 90 days was similar after versus before rescheduling (absolute risk difference, −1.1%; 95% CI, −2.3% to 0.1%; P = 0.084). The authors estimated the rescheduling rule to be associated with a 45.4-mg oral morphine equivalent increase (difference-in-differences estimate; 95% CI, 34.2–56.7 mg; P < 0.001) in initial opioid dispensing, a 4.1% absolute decrease (95% CI, −5.5% to −2.7%; P < 0.001) in refills within 30 days, and a 37.7-mg oral morphine equivalent increase (95% CI, 20.6–54.8 mg; P = 0.008) in opioids dispensed within 30 days. Conclusions: Among patients treated by surgeons who frequently prescribed hydrocodone before the Drug Enforcement Agency 2014 hydrocodone rescheduling rule, rescheduling did not impact long-term opioid receipt, although it was associated with an increase in opioid dispensing within 30 days of surgery. Abstract : Data derived from a large insurance database for a group of 10 common ambulatory orthopedic surgeries suggested that hydrocodone dispensing increased after rescheduling for the 30-day period after surgery. Data from the same source showed no difference in hydrocodone prescribing from 90 to 180 days after surgery.Supplemental Digital Content is available in the text.